Empowering Remote Vocational Schools with VocaTeach to Bridge Skills Gaps in the Era of Industry 4.0 and Society 5.0 - Yulianus Zega (Jurnal Vokasi Teknik Informatika, 2025)
This study presents the development and implementation of VocaTeach, a web-based application designed to enhance project-based learning in the context of automotive vocational education. Motivated by the growing need to align vocational training with Industry 4.0 competencies, VocaTeach integrates digital project management, collaboration tools, and a comprehensive evaluation system to support both teachers and students in managing complex, real-world automotive tasks. The system was developed using an Agile methodology and deployed at SMK Swasta Pembda Nias, a vocational school in a geographically remote region. A mixed-method approach was employed, combining surveys, interviews, and usage analytics to assess the platform’s effectiveness. Results showed a significant increase in student engagement (85%), peer collaboration (150% rise in interactions), and improved academic outcomes, including an 18% gain in theoretical test scores. Teacher workload decreased by up to 30%, reflecting improved efficiency in project supervision and assessment. Statistical analysis confirmed the significance of these improvements (p < 0.05) with a large effect size (Cohen’s d = 0.8). Qualitative data reinforced these findings, with students reporting enhanced motivation and perceived relevance of learning tasks, while teachers highlighted improved structure and fairness in assessment. The study concludes that VocaTeach is a viable and scalable digital innovation for vocational education, especially in underserved regions. Future research is recommended to explore integration with Industry 5.0 technologies and to evaluate long-term impacts on career readiness and skill mastery.